Psychological Traits of Patients With Depression Comorbid With Chronic Pain: Are Complaint and Competitive Tendency Related to Pain? - Koji Fujimoto; Masako Hosoi; Masako Hosoi; Masako Hosoi; Ryoko Katsuki; Toshio Matsushima; Keitaro Matsuo; Tomohiro Nakao; Nobuyuki Sudo; Nobuyuki Sudo; Nobuyuki Sudo; Takahiro A. Kato (Frontiers in Psychiatry, 2022)
BackgroundModern-Type Depression (MTD) is a category of depression that has been studied mainly in Japan; however, no study has attempted to determine its relation to chronic pain.AimTo determine possible associations between psychological traits related to MTD and the chronic pain of patients at psychiatric clinics.MethodTwo hundred and twenty-one first time patients who visited the psychiatric clinic at a Japanese university medical center or an associated clinic were enrolled. The Hamilton Depression Rating Scale was used to measure depressive symptoms. The 22-item Tarumi's Modern-Type Depression Trait Scale (TACS-22), Achievement Motive, and 20-item Toronto Alexithymia Scale were used to assess psychological traits related to depression and chronic pain. The clinical diagnosis of each patient was confirmed by use of the Structured Clinical Interview for DSM-IV Axis I Disorders, administered by experienced specialists. The medians of the psychological traits identified were compared between patients with or without chronic pain. Analysis was also done of patients with Major Depressive Disorder (MDD).ResultOf the 221 patients, 139 had chronic pain. Patients with chronic pain had more severe depressive symptoms, Alexithymia, and high scores for the complaint trait of MTD. Seventy-three of the 221 patients met the criteria for MDD (53 had chronic pain). Patients with MDD comorbid with chronic pain had a higher competitive achievement score, severe depression, and difficulty identifying feelings.ConclusionComplaint and competitive traits were shown to be related to chronic pain in psychiatric settings. Further study will allow us to design multidimensional approach for patients suffering from depression.